2018
DOI: 10.1108/ijif-09-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Analysing ar-rahnu in the context of informal credit market theory

Abstract: Purpose This study aims to offer a new area of discourse by investigating the factors determining the usage of the Islamic non-bank financing product ar-rahnu (Islamic pawnbroking) among women micro-entrepreneurs in Malaysia within the framework of the informal credit market theory. Design/methodology/approach The study is based on primary data obtained by using self-administered questionnaires distributed in three states in Malaysia: Kedah, Kelantan and Terengganu. The questionnaires were distributed to a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…On paper, Ar-Rahnu seems to be a better alternative to that of Islamic Micro-financing. As mentioned by Azman and Kassim (2018), Ar-Rahnu assists micro-entrepreneurs to diversify and enhance their businesses. In fact, it can be ensuring by offering the shari'ah compliancy product, the lowest service charges, near to potential customers, lenient on collateral and treat customer regardless their races or religious.…”
Section: Introductionmentioning
confidence: 99%
“…On paper, Ar-Rahnu seems to be a better alternative to that of Islamic Micro-financing. As mentioned by Azman and Kassim (2018), Ar-Rahnu assists micro-entrepreneurs to diversify and enhance their businesses. In fact, it can be ensuring by offering the shari'ah compliancy product, the lowest service charges, near to potential customers, lenient on collateral and treat customer regardless their races or religious.…”
Section: Introductionmentioning
confidence: 99%
“…Mohamad et al (2014) found that customers look for attractive safekeeping fees as another reason for them patronising the service. Due to that, ar-rahnu is becoming customers options which indirectly contribute towards financial performance of ar-rahnu (Abdul Razak, 2011;Azman et al, 2018;Mohammed et al, 2005;. The third element of acceptance that is positively correlated with financial performance is margin value.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ar-rahnu must give a competitive margin value. According to Nik Azman et al (2018), Agrobank ar-rahnu currently offers the highest margin value (80%), followed by both Pos Malaysia and Muassasah Gadaian Islam Terengganu at 75 per cent each. This indicates that, the higher the margin value given to customers, the better financial performance of arrahnu.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations